Pairwise Comparison Matrices and their Fuzzy Extension Multi-criteria Decision Making with a New Fuzzy Approach - Krejčí, Jana. (Cham : Springer International Publishing, 2018)
This book offers the first comprehensive and critical literature review of fuzzy pairwise comparison methods derived from methods originally developed for crisp pairwise comparison matrices. It proposes new fuzzy extensions of these methods and provides a detailed study of the differences and analogies between all the reviewed methods, as well as a detailed description of their drawbacks, with the help of many numerical examples. In order to prevent the drawbacks related to the reviewed fuzzy pairwise comparison methods, the book introduces constrained fuzzy arithmetic in fuzzy extension of the pairwise comparison methods. It proposes new fuzzy pairwise comparison methods based on constrained fuzzy arithmetic and critically compares them with the reviewed methods. It describes the application of the newly developed methods to incomplete large-dimensional pairwise comparison matrices showcased in a real-life case study. Written for researchers, graduate and PhD students interested in multi-criteria decision making methods based on both crisp and fuzzy pairwise comparison matrices, this self-contained book offers an overview of cutting-edge research and all necessary information to understand the described tools and use them in real-world applications.
Introduction -- Pairwise Comparison Matrices -- Fuzzy Set Theory -- Fuzzy Pairwise Comparison Matrices -- Incomplete Large-dimensional Pairwise Comparison Matrices -- Discussion and Future Research. .
Engineering
text file PDF
Keywords: Computational intelligence; Operations research; Management science; Artificial intelligence; Decision making